Race after Hitler : Black Occupation Children in Postwar Germany and America - Fehrenbach, Heide (Book collections on Project MUSE., 2007)
Heide Fehrenbach traces the complex history of German attitudes to race following 1945 by focusing on the experiences of and the debates surrounding the several thousand postwar children born to African American GIs and their German partners.